SOCIALIZATION OF SORT, STRAIGHTEN, SHINE, STANDARDIZE, SUSTAIN (5S) FOR UD. TIRTO AGUNG GRESIK - Hasly Puji Lestanto; Moch Sahri; Ilham Dafa Faniago; Hudzaifah Hamidy; Jerzi Rifansyah (Journal of Health Community Service, 2022)
Occupational Health and Safety (OHS) is important in all industrial sectors. The purpose of Occupational Health and Safety (OHS) is to improve and maintain the highest degree of all workers, both physically and mentally, and to ensure workers' welfare to prevent occupational diseases. UD. Tirto Agung is an informal industry that produces various types of cotton. UD. Tirto Agung Worker has 13 employees consisting of 7 women and six men divided into two work shifts. The practitioner's survey observed various potential hazards, namely noise, dust, poor lighting, and bad air temperature. From this problem, practitioners provide education about 5S (Sort, Straighten, Shine, Standardize, Sustain). This socialization aims to provide insight and knowledge about the 5S program, dust hazards, and practitioners providing personal protective equipment (PPE). The socialization results are successful because knowledge of Occupational Health and Safety (OHS) has increased from 13 workers, 10 of whom understand the dangers in the work environment and can implement 5S socialization in the workplace. In comparison, three workers have yet to be able to implement 5S in the work environment due to the influence of age.